2019
DOI: 10.3748/wjg.v25.i31.4414
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal motility and absorptive disorders in patients with inflammatory bowel diseases: Prevalence, diagnosis and treatment

Abstract: Inflammatory bowel diseases (IBD), Crohn`s disease and ulcerative colitis, are chronic conditions associated with high morbidity and healthcare costs. The natural history of IBD is variable and marked by alternating periods of flare and remission. Even though the use of newer therapeutic targets has been associated with higher rates of mucosal healing, a great proportion of IBD patients remain symptomatic despite effective control of inflammation. These symptoms may include but not limited to abdominal pain, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 106 publications
(112 reference statements)
1
25
0
1
Order By: Relevance
“…Such a situation is not rare, as acid-reducing agents are usually prescribed for functional dyspepsia, which is quite common, and UC patients are no exception. 15 Our data also showed that middle-aged patients were more often affected by administration of Asacol than younger patients. We did not assess the fecal excretion and mucosal concentration with 5-ASA.…”
Section: Discussionsupporting
confidence: 68%
“…Such a situation is not rare, as acid-reducing agents are usually prescribed for functional dyspepsia, which is quite common, and UC patients are no exception. 15 Our data also showed that middle-aged patients were more often affected by administration of Asacol than younger patients. We did not assess the fecal excretion and mucosal concentration with 5-ASA.…”
Section: Discussionsupporting
confidence: 68%
“…Ulcerative colitis (UC) is a non-specific chronic inflammatory bowel disease with diarrhea, abdominal pain, and bloody stool as the main clinical symptoms (Cooper et al, 1993;Pohjonen et al, 2019;Nishida et al, 2019). The lesions of UC are mainly in the mucosa or submucosa of the rectum and colon (Barros et al, 2019;Saw et al, 2019). In recent years, many clinical studies have confirmed that intestinal flora imbalance is closely related to ulcerative colitis (Xavier, 2016;Walujkar et al, 2018;Khan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The Rome IV classification system for functional gastrointestinal disorders (FGIDs) defines functional nausea in children and adolescents as bothersome nausea (a) occurring at least twice per week for at least two months as the primary symptom experienced, (b) not typically accompanied by vomiting, (c) not usually associated with meals, (d) not better explained by another diagnosis [ 3 ]. Functional nausea is a clinical diagnosis that is made after relevant evaluation for other possible underlying organic causes, such as inflammatory bowel disease [ 4 ], gastroparesis [ 5 ], eosinophilic esophagitis [ 6 ], celiac disease [ 7 ], and gastritis [ 8 ], has been reassuring.…”
Section: Introductionmentioning
confidence: 99%